Relationship Between Oxygen Saturation and Umbilical Cord pH Immediately After Birth - Sinan Uslu; Ali Bulbul; Emrah Can; Umut Zubarioglu; Ozgul Salihoglu; Asiye Nuhoglu (Elsevier, 2012)
The aim of this study is to determine the relationship between oxygen saturation (SpO2) by pulse oximetry levels and umbilical cord arterial pH values in healthy newborns during the first 15 minutes of life. Methods: The study was performed with healthy term, appropriate-for-gestational-age newborn infants. The infants were divided in two groups: umbilical cord arterial blood pH value ≤7.19 (group 1) and >7.19 (group 2); SpO2 levels during the first 15 minutes of life were compared between groups. Results: The study was completed with 129 infants (33 in group 1 and 96 in group 2). A significant correlation was found between first-measured preductal and postductal SpO2 levels by pulse oximetry and umbilical cord arterial pH values ([r2:0.72(0.62 -0.79); p < 0.001] and [r2:0.32(0.25 - 0.54); p < 0.001], respectively). In group 1, infants had lower SpO2 levels at both preductal and postductal measurements during the first 11 minutes of life and time to reach ≥90% SpO2 level was longer compared with infants in group 2. Conclusion: Determination of umbilical arterial blood pH values, in addition to clinical findings and oxygen saturation measurements, might be helpful in deciding the concentration of oxygen and whether or not to continue oxygen supplementation in the delivery room.